Using case study methodology to explore the role of discrimination in workplace incivility - Green, Cheryl (Journal of National Black Nurses' Association: JNBNA, 2018)
Exclusionary behaviors can be detrimental to the health and well-being of faculty in the workplace. When colleagues are judged by their peers because of the color of their skin, the language they speak, their gender, or who they choose to love (lesbian, gay, bisexual, transgender, asexual, or questioning), affected faculty are left emotionally and physically vulnerable. Institutions of higher learning must set standards of zero tolerance for faculty-to-faculty incivility. With standards taken from each faculty discipline, codes of conduct can be implemented not only at a departmental level, but also throughout the educational system.
Keywords: Discrimination; Exclusionary; Faculty; Humans; Incivility; Interprofessional Relations; Prejudice; dept.nur; peer-reviewed